RESEARCH ON TRANSIENTS AND CHOICE OF OPTIMUM PARAMETERS OF SWITCHING ELEMENTS FOR AN ELECTROMAGNETIC VALVE CONTROL FOR COMBUSTION ENGINE EXHAUST SAMPLING - O.V. Lavrinenko (National Technical University "Kharkiv Polytechnic Institute", 2014)
The article introduces a classical-method-based analysis procedure for transients in the control cascade of an electromagnetic valve for combustion engine exhaust sampling. Analytical expressions for currents and voltage on the cascade basic elements are obtained to allow specifying the optimal parameters of these elements in terms of speed and reliability.